2021
DOI: 10.1002/joa3.12639
|View full text |Cite
|
Sign up to set email alerts
|

Axillary vein access using ultrasound guidance, Venography or Cephalic Cutdown—What is the optimal access technique for insertion of pacing leads?

Abstract: Cardiac Implantable Electronic Device implantation is associated with a small risk for pocket hematoma partially due to inadvertent axillary/subclavian artery puncture, pneumothorax and infection and more rarely thoracic duct injury and brachial plexus injury and in the long term lead fracture. 1 The traditional anatomic based approach for subclavian vein puncture is particularly associated with an increased risk. 2,3 These risks could be reduced by accessing the axillary vein and not the subclavian vein using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Our shorter time to axillary venous access in the roadmap application reinforces the ndings of previous study which demonstrated in nonrandomized fashion a shorter time to position the leads in the superior vena cava using the ultrasound -guided axillary approach. [22,23] From a clinical point of view, longer procedure duration has been associated with increased infection risk, indicating that shorter duration interventions and lower incidence of complications, in addition to enabling quicker operating room turnover, may lead to better infective outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Our shorter time to axillary venous access in the roadmap application reinforces the ndings of previous study which demonstrated in nonrandomized fashion a shorter time to position the leads in the superior vena cava using the ultrasound -guided axillary approach. [22,23] From a clinical point of view, longer procedure duration has been associated with increased infection risk, indicating that shorter duration interventions and lower incidence of complications, in addition to enabling quicker operating room turnover, may lead to better infective outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Our shorter time to axillary venous access in the roadmap application reinforces the findings of previous study which demonstrated in nonrandomized fashion a shorter time to position the leads in the superior vena cava using the ultrasound -guided axillary approach. [22,23] From a clinical point of view, longer procedure duration has been associated with increased infection risk, indicating that shorter duration interventions and lower incidence of complications, in addition to enabling quicker operating room turnover, may lead to better infective outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoroscopic guided axillary vein cannulation has a 50% shorter venous access time (5.7 minutes) and 30% shorter total procedural time (34 minutes) compared to a cephalic cut-down, according to a prospective randomized study published in 2017. [12,13].…”
Section: Determining the Best Approachmentioning
confidence: 99%